Uso de materiais ilustrativos para comunicação ambiental da escola da Floresta no Sítio São João em São Carlos (SP) - Marchesin, Vitoria Martinelli (Universidade Federal de São Carlos, 2024)
This study explores the use of illustrative materials as a tool to enhance environmental communication at the Forest School, located at Sítio São João in São Carlos (SP). The Forest School welcomes thousands of visitors annually, including students and researchers, promoting educational activities focused on sustainability and environmental conservation. Given the need for clear and accessible communication for diverse audiences, this internship aimed to develop visual materials to convey information about the environmental practices implemented on the property. The methodology involved identifying key topics for environmental education at the site, creating a visual identity aligned with the project, and producing posters and infographics. Four main materials were developed: one on the “Sensory Trail,” which provides a sensory experience with nature; another on the “Water Reuse System,” which utilizes fish farming to irrigate crops; one about “Non-Conventional Food Plants” (NCFPs), highlighting their nutritional and cultural significance; and a final one on the “Meliponary,” emphasizing the conservation of native bees and their ecological role. The materials developed contribute to educational mediation, allowing visitors to engage more deeply with the environment while facilitating knowledge dissemination on sustainable practices. This work underscores the importance of visual resources in environmental communication and highlights the potential of Sítio São João as an educational space and a model for integrating educational tourism with environmental conservation.
Use of illustrative materials for environmental communication at the Forest school in Sítio São João, São Carlos (SP)
Keywords: Educação ambiental; Comunicação visual; Materiais ilustrativos; Turismo pedagógico; Sustentabilidade; Infografia; Environmental education; Visual communication; Illustrative materials; Educational tourism; Sustainability; Infographics; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL::FUNDAMENTOS DO PLANEJAMENTO URBANO E REGIONAL; CIENCIAS SOCIAIS APLICADAS::TURISMO; CIENCIAS SOCIAIS APLICADAS::COMUNICACAO